Respuesta :
Answer:
(-2, 0)
Step-by-step explanation:
y = 2x+4
6x - 3y = -12
Start by simplifying the second equation by dividing everything by 3 (this will make the math easier)...
2x - y = -4
Then, substitute 2x+4 for y into the second equation (this is because y = 2x+4)...
2x-3(2x+4)=-4
Distribute the -3
2x-3(2x)-3(4)=-4
2x-6x-12=-4
Combine like terms
-4x-12=-4
Add 12 to both sides
-4x-12+12=-4+12
-4x=8
Divide both sides by -4
x=-2
Plug -2 back in for x to solve for y:
y = 2(-2) + 4
y=-4+4
y=0
(x, y) = (-2, 0)
Answer:
Infinitely many solutions
Step-by-step explanation:
[tex]y=2x+4\\ [2] 6x-3y=-12[/tex] < ------------- Linear equations given
Equations Simplified or Rearranged :
[tex]y - 2x = 4 \\ [2] -3y + 6x = -12[/tex]
Solve by Substitution :
// Solve equation [1] for the variable [tex]y[/tex]
[tex][1] y = 2x + 4[/tex]
// Plug this in for variable[tex]y[/tex] in equation[tex][2][/tex]
[tex][2] -3*(2x+4) + 6x = -12[/tex]
[2] [tex]0 = 0 =>[/tex] Infinitely many solutions